Perilipin 1 expression differentiates liposarcoma from other types of soft tissue sarcoma - Straub, Beate Katharina; Pawella, Lena Maria; Renner, Marcus; Eiteneuer, Eva; Hashani, Merita; Schirmacher, Peter; Mechtersheimer, Gunhild (The American journal of pathology, 2019)
Lipid droplets, a morphologic feature of adipocytic tumors, are strongly regulated by associated proteins of the perilipin/PAT (perilipin, adipophilin, and tail-interacting protein of 47 kD) family. So far, the use of perilipins as markers for differential diagnosis of soft tissue tumors has only been studied in a few cases. The aim of this study was to investigate the expression of perilipins in 478 human soft tissue tumors and 60 respective normal tissues. Perilipin 1 was immunohistochemically positive in all studied cases of well-differentiated liposarcomas, >90% of myxoid round cell liposarcomas, and >70% of pleomorphic liposarcomas, whereas only the differentiated components of dedifferentiated liposarcomas were immunohistochemically positive for perilipin 1. All other types of soft tissue sarcomas were negative for perilipin 1. Perilipin 2 was more prominent in dedifferentiated and pleomorphic liposarcomas and nearly all other high-grade sarcomas. In well-differentiated liposarcomas, lipomas, or normal adipose tissue, perilipin 2 was virtually absent. In addition, long-term stimulation of adipogenesis in the liposarcoma cell line LiSa-2 restored perilipin 1 expression, as exhibited in the source tumor. Furthermore, knockdown of perilipin 2 or perilipin 3 in LiSa-2 cells influenced lipid droplet number and size as well as cell vitality. In summary, perilipin 1 is a promising marker for the differential diagnosis of liposarcomas from other soft tissue sarcomas, whereas perilipin 2 correlates negatively with tumor grade and may be therapeutically useful.
Gesehen am 12.09.2019